Smaller but Safer? - Stephanou, Constantinos (World Bank, Washington, DC, 2012)
Global trends taken for granted in recent decades, the big expansion in global financial assets compared with underlying economic activity, growing global financial integration, shrinking role of the state in financial systems, and rising share of cross-border ownership of financial institutions, may reverse over the foreseeable future. In addition, the structure of financial systems, particularly in developed countries, will likely become oriented less toward capital markets and more toward traditional (and simpler) banking activities. The impact on economic growth and overall welfare is likely to be negative, perhaps the price author have to pay for living in a brave new (and presumably safer) financial world.